Standardization and Quality Evaluation of Feather cum Skin Meal Prepared by Hydrothermal, Chemical and Biological Methods - Muzaffar, Zulhuma; Wani, Sarfaraz; Rather, Feroze; Khashoo, Zahid; Sofi, Asif; Kazmi, Asiya (Journal of Meat Science, 2017)
A study was under taken with the objective of standardizing the techniques for processing of feather-cum-skin meal and their effect on nutritive value. Broiler chicken feathers along with skin were washed and dried at 80±5oC in oven for 4-5 hours. Weighed samples were subjected to modified hydrothermal rendering (HT) alone and supplemented with chemical degradation (CT) and microbial degradation (MT). The meals were evaluated for nutritive quality in terms of proximate composition, mineral and amino acid profile. The quality of rendered fat was evaluated in terms of iodine value, peroxide value and free fatty acid value. The yield of fat and feather-cum-skin meal obtained after rendering was also estimated. The supplementation of CT and MT methods improved protein content of meal by 30 and 32 percent, respectively over HT method. The quality of the rendered fat was found satisfactory. It is concluded that CT or MT methods following HT method greatly improves the nutritive quality of feather cum skin meal besides providing good quality fat and can be used in industrial sector.
Keywords: Byproducts; Hydrothermal rendering; Feather meal; Chemical degradation; Microbial degradation